تحقيق المناط في التورق المصرفي المنظم في ضوء مقاصد الشريعة - بدادي, بوكة (جامعة الوادي university of eloued, 2016)
يكمن موضوع المقال في مدى مراعاة مقاصد الشريعة في المجال الاقتصادي والعمل المصرفي الإسلامي، وهذا بالنظر لأهمية هذا النشاط في تلبية الحاجات المادية والمالية، فأصبح من اللازم التعرف على أهم الوسائل التمويلية التي تتعامل بها مؤسسات الصيرفة الإسلامية، ثم عرضها على ميزان الشرع وهدي المقاصد. فكان موضوع التورق المصرفي المنظم باعتباره أبرز الأدوات التي تعرفها الساحة المالية المصرفية الإسلامية محور هذا المقال، وذلك لبيان حقيقته وحكمه. The article subject lies in the observance of the purposes of the law in the economic field and the work of Islamic banking, and that in view of the importance of this activity is to meet the physical and financial needs, it became necessary to identify the most important financial means to deal with the Islamic banking institutions, and then displayed on the balance Sharia and guidance purposes. This research paper deals for the subject of banking securitization structured as foremost among the tools that you know the financial arena of Islamic banking focus of this article, so as to indicate the truth and wisdom
مقال
Keywords: تحقيق المناط – التورق المصرفي المنظم – مقاصد الشريعة الإسلامية.; Tahkik El-manat - banking securitization structured - the purposes of Sharia.